1963
DOI: 10.1149/1.2425789
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Deposition of Silicon Oxide Films

Abstract: Silicon oxide films play an important role in semiconductor device technology. Surface passivation and diffusion masking are the most prominent applications for these amorphous films. There are several methods by which such oxide films may be obtained, but only the elevated temperature processes give satisfactory oxide films for the abovementioned applications.Decomposition of organic compounds on the absorption of energy is a well-known phenomenon. The necessary energy may be supplied as chemical energy, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Alternatively, the silicon dioxide films can be formed at low temperatures by rapid thermal oxidation (RTO), [14][15][16][17][18] plasma enhanced chemical vapour deposition (PECVD), [19][20][21][22] atomic-layer deposition (ALD), [23][24][25][26][27] atmospheric pressure chemical vapour deposition (APCVD), 22,28,29 nitric acid oxidation of silicon (NAOS), [30][31][32][33] and anodic oxidation. [34][35][36][37][38][39] The advantages and disadvantages of these different methods were discussed by Grant 40 who recently reported surface recombination velocities of less than 40 cm/s on silicon wafers passivated with silicon dioxide layers that were electrochemically grown in nitric acid at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the silicon dioxide films can be formed at low temperatures by rapid thermal oxidation (RTO), [14][15][16][17][18] plasma enhanced chemical vapour deposition (PECVD), [19][20][21][22] atomic-layer deposition (ALD), [23][24][25][26][27] atmospheric pressure chemical vapour deposition (APCVD), 22,28,29 nitric acid oxidation of silicon (NAOS), [30][31][32][33] and anodic oxidation. [34][35][36][37][38][39] The advantages and disadvantages of these different methods were discussed by Grant 40 who recently reported surface recombination velocities of less than 40 cm/s on silicon wafers passivated with silicon dioxide layers that were electrochemically grown in nitric acid at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The initial experiments using plasma in the CVD process dates back to 1950s and 1960s when the decomposition of organic compounds in the presence of an electron beam was first observed [8][9][10]. In the electro-optical systems, when a surface was exposed to an electron beam, it was covered by a thin film.…”
Section: History Of Pecvdmentioning
confidence: 99%
“…Upon observing this effect, researchers reasoned that the formation of the thin film was due to the interactions between the electron beam and organic vapor present in the vacuum system. They concluded that the mechanism of formation of the thin layer was the free radical polymerization of the organic molecules, upon exposure to the electron beam followed by adherence to the target surface [8][9][10]. After roughly a decade, Buck et al suggested that the observed mechanism of film formation can be beneficial for applications where thin insulating films were required [11].…”
Section: History Of Pecvdmentioning
confidence: 99%
See 1 more Smart Citation
“…The early papers by S. W. Ing [1][2][3] and co-workers, published between 1963 and 1965 on low-temperature, plasmaenhanced CVD (or simply PECVD) deposition of silicon oxide films, could be considered as one of the first experimental reports on the possibility of using electric discharges in gases to produce plasmas that generate various types of reactive species for thin film deposition. These initial attempts were used for microelectronic applications and, in particular, for diffusion masks and passivation.…”
Section: Introductionmentioning
confidence: 99%